LEARNING MEDIA USED WHEN LEARNING DISTANCE: ANALYSIS OF STRENGTHS AND WEAKNESSES OF GOOGLE CLASSROOM IN DISTANCE LEARNING - Atika Khovivah; M Theresia; N Utami; T Ardelia (ISER (Indonesian Science Education Research), 2021)
The Covid-19 pandemic has had a major impact on the order of life, especially in the world of education. Following Government Policy, the face-to-face teaching system is now being transferred to the online system or known as the online system. The problems that arise in choosing the right method to use in the teaching and learning process in the midst of thispandemic are a dilemma for teachers. Some of the alternative applications offered must be adapted to the conditions of the school, teachers and students. The application used must be able to be accessed and understood by every teacher and student so that learning objectives can be achieved. The focus of this research is the use of Google Classroom media in online learning and its advantages and disadvantages. Researchers conducted field research with a descriptive qualitative approach to the learning process in schools. The results show that online learning through Google Classroom has advantages and disadvantages. The advantages include that teachers can use various media for the learning process, both those contained in the Google Classroom or other media that can be linked to the classroom. While the drawbacks are network problems and the limited quota that students have can be an obstacle in the learning process, as well as the low level of student activity in the learning process. Almost 31 students who answered the questionnaire stated that Google Classroom was not very effective because it certainly could not replace face-to-face meetings. Because there are many things that cannot be done through google classroom.